Doctoral Graduates in Canada and the United States: Who Goes to North America for a Degree and Why - Daniel Boothby (Foresight and STI Governance, 2007)
The paper uses census data to examine employment and salaries of doctors in Canada and the U.S., as well as their mobility between the two countries. The main conclusions are: 1) the percentage of employment of doctors in the U.S. is significantly higher than in Canada, while in the U.S. educational sector, their concentration is significantly lower than in Canada; 2) income of doctors in the U.S., both in absolute terms and as the growth pace in the 1990's many times greater than earnings their Canadian colleagues; 3) an intense mobility of PhDs takes place between Canada and the USA; 4) in Canada compared to U.S. there are a higher percentage of doctors of foreign origin, which, however, does not cause a significant difference in the income of doctors between these two countries; 5) the most likely cause of such a gap - in slower growth in demand for doctors in Canada than in the U.S., 6), the gap between incomes of doctors of Canada and the United States increased over 1990 despite their considerable labor mobility. Possible explanations: a difference in the quality of training of doctors, lower incomes for those doctors who have recently immigrated to the United States, a strong dedication to their country of Canadian doctors.